Collaborative Strategy in Preventing the Vulnerability of Elderly Informal Workers - Endah Dwi Winarni; Ella Nurlela; Diana S. (Asian Social Work Journal, 2019)
The elderly who work in an informal sector tend to bear two layers of vulnerability: both body and mental functions that have been degenerated and the insecurities of the job. Status as an informal worker does have an impact on the uncertain income, also the absence of health benefits, pensions, or workers’ compensation. Even if the state guarantees social protections for the elderly, it still has a formidable challenge when it must to be provided for the elderly informal workers specifically, for example, a contribution-based pension that reaches more to the elderly formal workers. Thus, this study discusses the efforts in preventing the vulnerability of elderly informal workers, especially the elderly farmers who are chosen as a case’s subject in this study. Previous studies in a similar topic often emphasize the role of the state in preventing the vulnerability of elderly informal workers (a vertical scheme). In contrast to those studies, the argument of this study is the collaborative roles between the state and communities that are based on capability approach and social capital is able to prevent the vulnerability of elderly informal workers (vertical and horizontal synergy schemes). This study is written based on a case study research with the qualitative approach on the elderly farmers in Padamukti Village, Sukaresmi Subdistrict, Garut Regency, West Java, Indonesia.